Callus Induction and Establishing Cell Suspension Culture of Agastache J.Clayton Ex Gronov - Polivanova Oksana B.; Cherednichenko Mikhail Yu.; Khlebnikova Daria A. (BIO Web of Conferences, 2024)
The aim of this study was to initiate calli formation and cell suspension cultures from some species of Agastache genus. These plants could be useful for a production of bioactive secondary metabolites in vitro. For the initiation of callogenesis, two explant types were tested: leaf and stem explants from 40–60 days old in vitro seedlings. Percentage of callus formation was used as criterion to evaluate the efficiency of callus induction. Leaf- and stem-derived friable calli of A. foeniculum and A. urticifolia cultivated on MS medium supplemented with 0.5 mg/L 2.4-dichlorophenoxyacetic acid and 0.1 mg/L kinetin were selected for the cell suspension cultures establishing. The cell suspension cultures of A. foeniculum characterized by growth indexes of 1.08 and 8.57 for MS and B5 media respectively. For A. urticifolia suspension cultures growth indexes were 3.01 for MS medium and 1.29 for B5 medium. The period of culturing was 28 days. Viability of cell suspension cultures varied 50–100 during the period of culturing. According to the growth characteristics for establishing A. foeniculum suspension culture is better to use MS medium, and for A. urticifolia – B5.